2011
DOI: 10.1007/s00726-011-0874-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy, safety, and regulatory status of novel forms of creatine

Abstract: Creatine has become one of the most popular dietary supplements in the sports nutrition market. The form of creatine that has been most extensively studied and commonly used in dietary supplements is creatine monohydrate (CM). Studies have consistently indicated that CM supplementation increases muscle creatine and phosphocreatine concentrations by approximately 15-40%, enhances anaerobic exercise capacity, and increases training volume leading to greater gains in strength, power, and muscle mass. A number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
202
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(222 citation statements)
references
References 54 publications
4
202
0
16
Order By: Relevance
“…Only during the accelerated stability test was there a small indication of creatine to creatinine conversion at 0.055 after 150 days, the equivalent to 5 years of real time, and 0.1% after 180 days, the equivalent to 6 years of realtime. It has been established that creatine breakdown is a function of pH [2]. Using a systematic mock-up of a stomacher, described above, it was shown that Kre-Alkalyn maintained a significantly higher pH than traditional creatine, in three separate reagents tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only during the accelerated stability test was there a small indication of creatine to creatinine conversion at 0.055 after 150 days, the equivalent to 5 years of real time, and 0.1% after 180 days, the equivalent to 6 years of realtime. It has been established that creatine breakdown is a function of pH [2]. Using a systematic mock-up of a stomacher, described above, it was shown that Kre-Alkalyn maintained a significantly higher pH than traditional creatine, in three separate reagents tested.…”
Section: Resultsmentioning
confidence: 99%
“…Creatine (N-(aminoiminomethyl-N-methyl glycine) is an important energy producing amino acid based metabolite produced in the liver, kidneys, and pancreas and commonly used by the muscles [1][2][3]. Creatine in various forms is used as a supplement to increase athletic performance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a slight increase (within the normal range) of urinary methylamine and formaldehyde excretion after a high dose of Cr, although this is reduced when the dose is spread throughout the day (Kim et al 2011). The most commonly used form of Cr is creatine monohydrate (CrM) (Jäger et al 2011). Studies have shown that little or no CrM is degraded during normal digestion and that nearly 99% of orally administered CrM is either taken up by muscle or excreted in urine.…”
Section: Introductionmentioning
confidence: 99%
“…These newer forms have been purported to have better physical and chemical properties, bioavailability, efficacy, and/or safety profiles than CrM. However, there is no evidence that any of these are more effective and/or safer than CrM, whether ingested alone and/or in combination with other nutrients (Jäger et al 2011). Furthermore, the regulatory position of these newer forms is uncertain in many countries, whereas that for CrM is clear.…”
Section: Introductionmentioning
confidence: 99%